Regionale Differenzierung der Wirtschaftskraft in Italien - Monheim, Rolf (ERDKUNDE, 1974)
A series of maps is used to illustrate the regional structure and dynamics of the Italian economy 1951-71. The contrast between Northern and Southern Italy remains, although the conventional mean values for the two parts of the country and the use of administrative regions as a statistical base hides important differences. In the North, economic strength is more evenly distributed. In the South, on the other hand, economic growth is concentrated in a few already favoured areas, while the weaker parts of the area are only averagely in relative terms and far below average in absolute terms. In this way, dualistic structures have come into existence within Southern Italy. Cartographic evalua tion of the indices of purchasing power worked out by Tagliacarne in the ’Carta Commerciale d’ltalia’ enables analysis, on a small area basis, of the economic strength of 654 functionally demarcated spatial units. Per capita pur chasing power shows a gradient between town and country, north and south, lowlands and mountain areas. In terms of purchasing power volume, the North shows a dense network of important centres, whereas the South has weaker, more isolated centres. The attractive power of centres is less in the South. The map allows recognition, not only of the economic backwardness of Southern Italy but also of the weaknesses in its central place system